Well production forecasting based on ARIMA-LSTM model considering manual operations. (1st April 2021) - Fan, Dongyan; Sun, Hai; Yao, Jun; Zhang, Kai; Yan, Xia; Sun, Zhixue
Abstract: Accurate and efficient prediction of well production is essential for extending a well's life cycle and improving reservoir recovery. Traditional models require expensive computational time and various types of formation and fluid data. Besides, frequent manual operations are always ignored because of their cumbersome processing. In this paper, a novel hybrid model is established that considers the advantages of linearity and nonlinearity, as well as the impact of manual operations. This integrates the autoregressive integrated moving average (ARIMA) model and the long short term memory (LSTM) model. The ARIMA model filters linear trends in the production time series data and passes on the residual value to the LSTM model. Given that the manual open-shut operations lead to nonlinear fluctuations, the residual and daily production time series are composed of the LSTM input data. To compare the performance of the hybrid models ARIMA-LSTM and ARIMA-LSTM-DP (Daily Production time series) with the ARIMA, LSTM, and LSTM-DP models, production time series of three actual wells are analyzed. Four indexes, namely, root mean squared error (RMSE), mean absolute error (MAE), mean absolute percentage error (MAPE), and similarity (Sim) values are evaluated to calculate the prediction accuracy. The results of the experiments indicate that the single ARIMA model has a good performance in the steady production decline curves. Conversely, the LSTM model has obvious advantages over the ARIMA model to the fluctuating nonlinear data. And coupling models (ARIMA-LSTM, ARIMA-LSTM-DP) exhibit better results than the individual ARIMA, LSTM, or LSTM-DP models, wherein the ARIMA-LSTM-DP model performs even better when the well production series are affected by frequent manual operations. Graphical abstract: Fig. 1 Schematic diagram of graphical Abstract. Image 1 Highlights: New hybrid models (ARIMA-LSTM, ARIMA-LSTM-DP) for predicting oil and gas well production time series. Fewer and frequent manual operations are investigated as nonlinear inputs for LSTM model. The new forecasting approach is applied to production time series of three actual wells.